Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's consider the given information:
1. [tex]\( i = \sqrt{-1} \)[/tex]
To find [tex]\( i^2 \)[/tex]:
2. By definition, squaring both sides of the equation [tex]\( i = \sqrt{-1} \)[/tex] gives us:
[tex]\[ i^2 = (\sqrt{-1})^2 \][/tex]
3. Squaring a square root undoes the square root function, so:
[tex]\[ (\sqrt{-1})^2 = -1 \][/tex]
Therefore, the expression [tex]\( i^2 \)[/tex] evaluates to:
[tex]\[ i^2 = -1 \][/tex]
So, the completed expression is:
[tex]\[ i^2 = -1 \][/tex]
1. [tex]\( i = \sqrt{-1} \)[/tex]
To find [tex]\( i^2 \)[/tex]:
2. By definition, squaring both sides of the equation [tex]\( i = \sqrt{-1} \)[/tex] gives us:
[tex]\[ i^2 = (\sqrt{-1})^2 \][/tex]
3. Squaring a square root undoes the square root function, so:
[tex]\[ (\sqrt{-1})^2 = -1 \][/tex]
Therefore, the expression [tex]\( i^2 \)[/tex] evaluates to:
[tex]\[ i^2 = -1 \][/tex]
So, the completed expression is:
[tex]\[ i^2 = -1 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.